Understanding pathophysiology - Huether, Sue E.; McCance, Kathryn L. (Elsevier, 2012)
Enables you to learn the essential concepts of pathophysiology and offers information on treatments, manifestations, and mechanisms of disease. This title delivers the information on the disease process across the lifespan, giving you the fundamental knowledge you need to move forward in your nursing education.